Dynamic Archive Management Analysis at The Regional Revenue Agency of Riau Province - Purnama, Vella; Museliza, Virna (International Conference on Business Management and Accounting, 2024)
Several problematic phenomena related to archive management were found in the Riau Province Regional Revenue Agency, namely the accumulation of archives for too long, lack of archivists and the existence of archive employees who have not received archiving training, limited space, and delays in completing secretarial tasks related to documents. These obstacles will certainly hinder good archive management so that the archives needed are difficult to find. This study aims to: (1) find out and analyze how dynamic archives are managed in the Riau Province Regional Revenue Agency; and (2) find out what is in the Riau Province Regional Revenue Agency. This study is qualitative. Research data was collected using interview techniques, and supported by documentation and observation. Through the results of the study, it can be concluded that: (1) the management of dynamic archives in the Riau Province Regional Revenue Agency is by Government Regulation Number 28 of 2012 concerning Archives, namely including the creation of archives, use of archives, storage of archives and reduction of archives; (2) Obstacles in the process of managing dynamic archives at the Riau Province Regional Revenue Agency include the length of the archive recording process due to the limited number of employees who record and process archives, the process of registering archive loans which does not use computers, and the uneven capacity of HR for archive managers at the Riau Province Bapenda.